Synthesis, characterisation and pre-evaluation of a novel terpolymer as pour point depressants to improve the Malaysian crude oil flowability - Ibrahim, Elganidi; Basem, Elarbe; Norida, Ridzuan; Norhayati, Abdullah (Springer Science and Business Media Deutschland GmbH, 2022)
Wax deposition is considered one of the most serious operational issues in the crude oil pipelines. This issue occurs when the crude oil temperature decreases below the temperature of wax appearance and paraffin wax starts to precipitate on the pipelines’ inner walls. As a result, the crude oil flow is impeded because of the precipitated wax. The use of polymeric pour point depressants has obtained significant interest among researchers as an approach of wax control for enhancing the flowability of the waxy crude oil. PPD of poly(behenyl acrylate -co-stearyl methacrylate-co- maleic anhydride) (BA-co-SMA-co-MA) was facilely synthesised by the use of free radical polymerisation. The variation of the PPD structure was studied by choosing several essential parameters like monomers ratio, reaction time, initiator concentration, and reaction temperature. Furthermore, viscosity measurement, pour point, and cold finger apparatus have been employed to evaluate the efficiency of the synthesised Polymer. The chemical structure of poly(BA-co-SMA-co-MA) has been identified through the use of Fourier transform infrared as well as nuclear magnetic resonance. The experimental findings demonstrated that the ideal conditions for obtaining the highest yield were 1.5% initiator concentration, reaction time and temperature of 8 h and 100 °C, respectively, and monomer ratio of 1:1:1 (BA:SMA:MA). Under these ideal conditions, the prepared terpolymer reduced the crude oil viscosity at 30 °C and 1500 ppm from 7.2 to 3.2 mPa.s. The cold finger experiment demonstrated that after poly(BA-co-SMA-co-MA) was used as a wax inhibitor, the maximum efficiency of paraffin inhibition of 45.6% was achieved at 200 rpm and 5 °C. Besides, the best performance in depressing the pour point by ΔPP 14 ℃ observed at the concentration of 1500 ppm, which can change the growth characteristics of wax crystals and delay the aggregation of asphaltene and resin, thus effectively improving the flowability of crude oil.